Perbedaan Hasil Belajar Menggunakan Model Pembelajaran Discovery Learning Berbantu Aplikasi Quizizz dengan Pembelajaran Konvensional - Oknaryana Oknaryana; Vina Oktaviani; Haris Kurniawan (Universitas Negeri Padang, 2023)
This study aim to compare learning outcomes in Class XI SMAN 1 Pantai Cermin using the Quizizz Aplication-assisted Discovery Learning learning model versus the Conventional learning model. A quasi-experimental design, purposive sampling technique, instrument testing, gain score, validity, reliability, different test questions, and level of difficulty were all used in the study. Data collection and documentation, as well as learning outcomes tests This study's population was class XI IPS SMA N 1 Pantai Cermin, with samples XI IPS 3 for the experimental class and XI IPS 2 for the control class. The paired sample t-test and independent sample t-test analysis methods were used. The study found that there are differences in student learning outcomes when using the Quizizz Aplication assisted Discovery Learning learning model versus traditional methods.